Microsecond linear optical response in the unusual nematic phase of achiral bimesogens - VIJ, JAGDISH; BALACHANDARAN, RESHMA; NAGARAJ, MAMATHA; PANOV, VITALI (My University, 2011)
Some hydrocarbon linked mesogenic dimers are known to exhibit an additional nematic phase (N(x)) below a conventional uniaxial nematic (N(u)) phase. Although composed of non-chiral molecules, the N(x) phase is found to exhibit linear (polar) switching under applied electric field. This switching has remarkably low response time of the order of a few microseconds. Two chiral domains with opposite handedness and consequently opposite responses are found in planar cells. Uniformly lying helix, electroclinic, and flexoelectric effects are given as possible causes for this intriguing phenomenon.
PUBLISHED
Keywords: Physical chemistry; chirality; flexoelectricity; nematic liquid crystals; Nanoscience & Materials